2019
DOI: 10.1111/srt.12730
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy and histological features of depigmentation after local corticosteroid injection

Abstract: Background Clinically, depigmentation after local corticosteroid injection is not rare. But there are less articles about its reflectance confocal microscopy (RCM) and histological features. This study aimed to define the RCM features and histopathologic findings of hypopigmentation after local corticosteroid injection and to analyze the correlations between the above two methods. Methods Forty cases with hypopigmentation after local corticosteroid injection were used to analyze the clinical and RCM features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…23 Application of vitamin E paste and exposure of narrow ultraviolet rays for half a year were used to treat hypopigmentation in the study by Gu et al However, this treatment yielded a slow regression (82.50%) or consistent result (17.50%) in a year of follow-up duration. 25 Fat grafting, serial normal saline infiltration, and temporal fascia implantation are a few of the treatment options that may be considered with regard to refractory subcutaneous fat atrophy. 23 Subcutaneous fat atrophy and skin hypopigmentation associated with triamcinolone injection have been reported to affect several injection sites, depending on the location of the injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Application of vitamin E paste and exposure of narrow ultraviolet rays for half a year were used to treat hypopigmentation in the study by Gu et al However, this treatment yielded a slow regression (82.50%) or consistent result (17.50%) in a year of follow-up duration. 25 Fat grafting, serial normal saline infiltration, and temporal fascia implantation are a few of the treatment options that may be considered with regard to refractory subcutaneous fat atrophy. 23 Subcutaneous fat atrophy and skin hypopigmentation associated with triamcinolone injection have been reported to affect several injection sites, depending on the location of the injection.…”
Section: Discussionmentioning
confidence: 99%
“…This might be caused by inhibition of prostaglandin or cytokine production in epidermal cells and suppression of a secretory metabolic product from melanocytes. 16,25 Concerning subcutaneous fat atrophy, it has been suggested that the corticosteroids have antiproliferative effects on keratinocytes and fibroblasts. It is also known that corticosteroid alters the metabolism of extracellular matrix proteins and the synthesis of lipids in the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation